Winter wheat productivity and grain quality while minimizing agricultural techniques in the conditions of the Central Blackearth Region - I. I. Gureev; A. V. Gostev; L. B. Nitchenko; V. A. Lukiyanov; S. V. Khlyupina; I. A. Prushchik (Зерновое хозяйство России, 2023)
Winter wheat is the main grain crop in the Central Blackearth region. The purpose of the current study was to estimate the effect of basic tillage practices and doses of mineral fertilizers in crop rotations on the productivity, grain quality and economic efficiency of winter wheat grain production in the conditions of the Central Blackearth region. The study was carried out on the experimental field of the FSBSI “Kursk FARC” on the slope of the northern exposure in 2016–2020. The scheme of the trial included crop rotations (grain-fallow, grain-grass-fallow, graingrass), primary tillage methods (plowing, disking, non-moldboard plowing), mineral fertilizers (without fertilizers, single N20Р40К40 and double N40Р80К80 doses). As a result of the study, there has been established productivity advantage of the grain-fallow crop rotation over the grain-grass-fallow and grain-grass crop rotation. Winter wheat productivity in the grain-grass crop rotation has decreased on an average of 10.2 %, in the grain-grass it has reduced on 15.8 %, compared with the grain-fallow crop rotation. The minimization of primary tillage methods in most cases has contributed to a decrease of winter wheat productivity, content of gluten, protein, and grain nature weight, compared with plowing. The introduction of mineral fertilizers has contributed to the improvement of all indicators of winter wheat grain quality. The largest yield of 4.63 t/ha was obtained in a grain-fallow crop rotation when plowing the soil with a fertilizer dose of N40P80K80. Calculations of the economic efficiency of the applied technologies have shown that the cost price of winter wheat grain was lower (4.44 thousand rubles/t) when disking soil in a grain-grass crop rotation with the application of a fertilizer dose N20P40K40. At the same time, the profit has amounted to 19.85 thousand rubles/ha, the level of profitability was 125.2 %. The minimum cost price of winter wheat grain was found in the variant with a fertilizer dose of N32P64K64.